Program Piket Bergilir Mengganti Tempel Nadzam Hafalan untuk Menanamkan Nilai Tanggung Jawab Santri Pondok Pesantren At-Taroqqi Karongan Sampang - Ach. Fatoni; Muhammad Yusron Maulana El-Yunusi (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Rotating Task Program to Replace Memorization Nadzam Stickers to Instill Responsibility Values ​​in Students of At-Taroqqi Karongan Sampang Islamic Boarding School is an effort to shape the character of students through responsibility for memorization of nadzam in the Islamic boarding school. In implementing this activity, students are given the task of rotating to replace memorization nadzam stickers every week which is a symbol of strengthening memorization and discipline. This program aims to instill the values ​​of responsibility, discipline, and cooperation between students, while improving the quality of memorization of nadzam as part of religious education at At-Taroqqi Islamic Boarding School. This activity is expected to have a positive impact on the development of students' character, strengthen their attachment to the values ​​of the Islamic boarding school, and increase their success in memorizing and studying nadzam. The implementation of this program involves supervision from the Islamic boarding school supervisor and active participation from students in every process. Through this program, it is expected that students can develop maturity, a sense of responsibility, and a disciplined attitude that will be useful for their lives in the future.